Cordyceps cateniannulata, a new potential strain for controlling Allantus luctifer from China - Zhang, Xiaona; Wu, Yu; Peng, Xue; Liu, Can; Yang, Guimin; Chen, Qingfu; Jin, Daochao (PeerJ, 2024)
Allantus luctifer is one of the most serious pests of buckwheat, with its larvae mainly damaging leaves during the seedling and flowering stages. Entomogenous fungi play a crucial role as biological regulators of arthropod populations in nature. In this paper, a newly isolated strain 19GZAl-1, was identified as Cordyceps. cateniannulata through the observetions of macroscopic and microscopic morphological features, and the results of rDNA- ITS sequence alignment and phylogenetic analysis. By comparing the efficacy of ten entomopathogenic fungal strains, including six strains of C. cateniannulata and four other Cordyceps species, against A. luctifer larvae, the new strain 19GZAl-1 exhibited the highest mortality rate. Mortality rates of A. luctifer larvae treated by spraying with the strain 19GZAl-1 increased as larval stage decreased, with first instar larvae showing the highest mortality rate of 85%. The appressorium from conidia invaded the larval body through areas with thin cuticle, such as larva pod base and internode folds, after which the hyphae grew rapidly, filling the haemocoel, and finally protruding from the integument upon melanization and decomposition of the intestinal wall cells. The results suggest that the strain 19GZAL-1 of C. cateniannulata has potential against A. luctifer larvae, which is significant for further study on the infection mechanism of C. cateniannulata on insects.
Keywords: Cordyceps cateniannulata; Mortality; Biological control; Histopathology; Allantus luctifer